2015
DOI: 10.1111/caim.12122
|View full text |Cite
|
Sign up to set email alerts
|

How Resource Challenges Can Improve Firm Innovation Performance: Identifying Coping Strategies

Abstract: Researchers recently suggested that challenges in the form of adversities and constraints can actually promote individuals, teams and firms. However, it remains unclear how such challenges elicit positive innovation performance. Moreover, we still cannot distinguish between the conditions under which challenges enhance or hinder firm innovation performance. In this paper, we review the literature on coping with a specific and central type of challengeresource challenge, such as a lack of financial or human res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 130 publications
(170 reference statements)
0
12
0
Order By: Relevance
“…Third, our striking findings regarding managerial experience show that sufficient experience is a key boundary condition for the inducement effect of resource constraints on internal efficiency frugal innovations (Type 1), but actually has no effect for external constraints on Type 2 frugal innovation. If an effective search response induced by constraints may be conditional on the presence of enough capabilities to recognise the problem and opportune search pathways, it could explain why so far the literature of problemistic search (Posen et al, 2018) and resource constraint-induced innovation (Rosenzweig & Grinstein, 2016) has suffered from a relatively high degree of inconsistent findings. By including the managerial experience, or more broadly the capabilities and cognition fields, future work into problemistic search could potentially yield more consistent findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, our striking findings regarding managerial experience show that sufficient experience is a key boundary condition for the inducement effect of resource constraints on internal efficiency frugal innovations (Type 1), but actually has no effect for external constraints on Type 2 frugal innovation. If an effective search response induced by constraints may be conditional on the presence of enough capabilities to recognise the problem and opportune search pathways, it could explain why so far the literature of problemistic search (Posen et al, 2018) and resource constraint-induced innovation (Rosenzweig & Grinstein, 2016) has suffered from a relatively high degree of inconsistent findings. By including the managerial experience, or more broadly the capabilities and cognition fields, future work into problemistic search could potentially yield more consistent findings.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was investigated for the case of resource constraints in general, where research showed that resource constraints can indeed induce innovations, in particular so in small, competitive markets and product domains where no major capital investments are required (Katila & Shane, 2005). A second body of literature focuses on the role of resource constraints as opportunities for entrepreneurs, creating efficient and affordable products and services that help their customers deal with these resource constraints (Navi et al, 2012;Rosenzweig & Grinstein, 2016). While both bodies of literatures use the concept of resource constraint, they are conceptually not the same.…”
Section: Resource Constraints As Drivers Of Frugal Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, discussions regarding customer orientation are impossible without innovation, and these categories depend on the decision of the leader (e.g. Rosenzweig & Grinstein, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is a concrete example of how to manage idea competitions to overcome the existing cultural patterns of innovation (Erickson et al, 2012;Zuchowski et al, 2016). However, such cultural changes often require long-term objectives, as it requires time to develop and cultivate capabilities for innovation (Rosenzweig & Grinstein, 2016).…”
Section: Narrow Success Focusmentioning
confidence: 99%